Non-neovascular pachychoroid disease mimicking exudative age-related macular degeneration - Thachpacha Kaseewat (2022)
Purpose: To describe a case of pachychoroid disease most compatible with central serous chorioretinopathy (CSC) presented with a large relapsing retinal pigment epithelial detachment (PED) associated with only a small amount of subretinal fluid (SRF) in the background of macular drusen in an elderly patient mimicking neovascular age-related macular degeneration (AMD). Methods: This was a review of 32 months of the clinical course and findings on multimodal imaging including fundus photography, optical coherence tomography, fundus fluorescein angiography (FFA), indocyanine green angiography (ICGA), and optical coherence tomography angiography (OCTA). Results: A large relapsing PED sometimes with small amount of SRF at its apex was found in the background of macular drusen in the right eye of a 63-year-old Thai woman. The relapses of the PED showed an apparent association with recent steroid exposure. Multimodal imaging demonstrated the characteristics of pachychoroid diseases with pachyvessels and choroidal hyperpermeability. The PED and SRF responded well to anti-vascular endothelial growth factor (anti-VEGF) therapy, especially aflibercept, but could also be spontaneously resolved without anti-VEGF. No evidence of choroidal neovascularization or polyps could be identified by serial FFA, ICGA, and OCTA even when the retinal pigment epithelium was completely flat with no obscuration by PED. Conclusions: A large PED with little SRF could present signs of CSC. This clinical presentation could be confused with neovascular AMD, and multimodal retinal imaging was crucial to guide correct diagnosis and management.